Microwave-assisted regioselective direct C–H arylation of thiazole derivatives leading to increased σ1 receptor affinity. Issue 2 (18th December 2015) - Kokornaczyk, Artur; Schepmann, Dirk; Yamaguchi, Junichiro; Itami, Kenichiro; Wünsch, Bernhard
Abstract : Regioselective direct CH arylation of2a led to thiazoles2b and2c with a 4-tolyl moiety in C5- and C4-position displaying 5- to 9-fold increased σ 1 affinity. Abstract : New thiazole analogues2 of spirocyclic thiophenes1, which are known to show high σ 1 receptor affinities, have been developed as potentially better σ 1 receptor ligands. To introduce an aryl group onto the thiazole core of2 (C4 or C5 positions), we used Pd-catalyzed regioselective C–H arylation reactions. The Pd-catalyzed C5 arylation of2a could be considerably improved by using microwave irradiation technique. The Pd-catalyzed C4 arylation of thiazole2a with arylboronic acid6 could be achieved in the presence of Pd(OAc)2, 1, 10-phenanthroline, TEMPO, and LiBF4 . Under these conditions, the tertiary amine and the tertiary alcohol were well-tolerated. The regioselective arylation of2a led to new compounds2b and2c, with a 4-tolyl moiety in the C5- and C4-positions, displaying five to nine-fold increased σ 1 affinity. The same σ 1 affinity of the regioisomeric thiazoles2b and2c can be explained by fast rotation around the piperidine–thiazole bond. Compared to spirocyclic thiophenes1, thiazoles2 are considerably more polar.